1992
DOI: 10.1289/ehp.929759
|View full text |Cite
|
Sign up to set email alerts
|

Overview of pulmonary alveolar macrophage renewal in normal rats and during different pathological processes.

Abstract: We& report experimental results on pulmonary alveolar macrophage (PAM) renewal in healthy rats and in rats treated with particles introduced in the lungs. Morphometric studies showed that the lungs of normal rats of the strain used in our study contain 20 x 10' PAM, 50 x 10' monocytes in alveolar capillaries, and about 3 x 10' interstitial macrophages.Pulse labeling with a tritiated thymidine (3HI) gave a labeling index of OA% for the monocytes, of which a few could be observed in mitosis within alveolar capiH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In addition, dendritic cells become refractory to subsequent stimulation (40). Furthermore, alveolar macrophages are essentially nondividing cells (41) and display a relatively long turnover time (42,43) and thus become refractory relatively easily. This results in a diminished cellular recruitment, prevents diseaseinduced weight loss and lung pathology, but still allows pathogen clearance.…”
Section: Refractory Microenvironmentmentioning
confidence: 99%
“…In addition, dendritic cells become refractory to subsequent stimulation (40). Furthermore, alveolar macrophages are essentially nondividing cells (41) and display a relatively long turnover time (42,43) and thus become refractory relatively easily. This results in a diminished cellular recruitment, prevents diseaseinduced weight loss and lung pathology, but still allows pathogen clearance.…”
Section: Refractory Microenvironmentmentioning
confidence: 99%
“…Alveolar macrophages are capable of proliferating in vitro in the presence of the appropriate molecular growth factors (Akagawa et al, 1988;Lin et al, 1989), in contrast to expectations for terminally differentiated cells. Also, in vivo labelling studies have shown that roughly 3% of alveolar macrophages are synthesizing DNA in preparation for cell division at any given time (Blusse van Oud Alblas et al, 1983;Coggle and Tarling, 1984;Fritsch and Masse, 1992), but the authors disagree about which cells are dividing. Several theories for the origin of alveolar macrophages have been proposed and investigated:…”
Section: Alveolar Macrophage Dynamicsmentioning
confidence: 99%
“…(1) alveolar macrophages derive from migrating blood monocytes, and are normally incapable of dividing (Blusse van Oud Alblas and van Furth, 1979); (2) monocytes mature in lung capillaries and undergo a final maturation division in the alveoli (Fritsch and Masse, 1992); (3) alveolar macrophages derive from interstitial macrophages through local division and maturation (Bowden, 1984); (4) alveolar macrophages divide in situ (Coggle and Tarling, 1984;Shellito et al, 1987).…”
Section: Alveolar Macrophage Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations